Cartografy in aid territorial planning of the urban municipality of Garanhuns-PE - Costa, Samuel Othon de Souza; França, Elaynne Mirele Sabino de; Lima, Carlos Eduardo Santos de; Lima, Djenane Regina Maia de; Gomes, Daniel Dantas Moreia (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The following paper aims to present cartographic information produced to aid the management of the urban area of Garanhuns, in interior of Pernambuco, a distance of 228 km from the capital, Recife. Remote sensing has as one of its principles, agility and objectivity in obtaining data and images and can be used in urban planning, considering a lot of information to be processed, analyzed and integrated. Satellite images, available by INPE and Google earth, which were treated with the software ARCGIS 10.2.2, aiming to improve the visualization and representation of the images were used. The production of a base map of the municipality of Garanhuns, aided by information provided by the IBGE, allow us a better understanding of the urban area, where as the processes of development and identifying the strengths and limitations of urban use, comprising thus significant results for management and improvement of the city ’s Master Plan of the city.